Significance and Relevance of Spermatozoal RNAs to Male Fertility in Livestock - Sahoo, Bijayalaxmi; Choudhary, Ratan K.; Sharma, Paramajeet; Choudhary, Shanti; Gupta, Mukesh Kumar (Frontiers in Genetics, 2021)
Livestock production contributes to a significant part of the economy in developing countries. Although artificial insemination techniques brought substantial improvements in reproductive efficiency, male infertility remains a leading challenge in livestock. Current strategies for the diagnosis of male infertility largely depend on the evaluation of semen parameters and fail to diagnose idiopathic infertility in most cases. Recent evidence show that spermatozoa contain a suit of RNA population whose profile differs between fertile and infertile males. Studies have also demonstrated the crucial roles of spermatozoal RNA (spRNA) in spermatogenesis, fertilization, and early embryonic development. Thus, the spRNA profile may serve as unique molecular signatures of fertile sperm and may play pivotal roles in the diagnosis and treatment of male fertility. This manuscript provides an update on various spRNA populations, including protein-coding and non-coding RNAs, in livestock species and their potential role in semen quality, particularly sperm motility, freezability, and fertility. The contribution of seminal plasma to the spRNA population is also discussed. Furthermore, we discussed the significance of rare non-coding RNAs (ncRNAs) such as long ncRNAs (lncRNAs) and circular RNAs (circRNAs) in spermatogenic events.